2018
DOI: 10.3390/molecules23051030
|View full text |Cite
|
Sign up to set email alerts
|

Transient Sulfenic Acids in the Synthesis of Biologically Relevant Products

Abstract: Sulfenic acids as small molecules are too unstable to be isolated and their transient nature offers the possibility to involve them in concerted processes that lead to the obtainment of functional groups such as sulfoxides, sulfones, and disulfides. All these functions are present in a number of natural and synthetic drugs and can represent structural motives inducing biologically relevant properties. In this small review the generation and reactions of sulfenic acid bearing naturally occurring residues are de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…To investigate the feasibility of this concept, we utilized sulfoxides as caged precursors to small molecule sulfenic acids (Table 2). This decaging reaction typically requires heat but can take place at ambient temperatures when the β-carbon is connected to strong electron withdrawing groups (EWGs) 37,38 . To study the effect of EWGs, we prepared several thioether precursors (12)(13)(14), and used hypochlorous acid (HOCl)a powerful oxidant produced by biological systems as an immune response -to convert them to sulfoxides.…”
Section: Redox-triggered In Situ Tpp Generation For Mitochondrial Delmentioning
confidence: 99%
“…To investigate the feasibility of this concept, we utilized sulfoxides as caged precursors to small molecule sulfenic acids (Table 2). This decaging reaction typically requires heat but can take place at ambient temperatures when the β-carbon is connected to strong electron withdrawing groups (EWGs) 37,38 . To study the effect of EWGs, we prepared several thioether precursors (12)(13)(14), and used hypochlorous acid (HOCl)a powerful oxidant produced by biological systems as an immune response -to convert them to sulfoxides.…”
Section: Redox-triggered In Situ Tpp Generation For Mitochondrial Delmentioning
confidence: 99%
“…Further increasing the reaction temperature raised the yield of 3 aa to 73 % (Table 1, entry 4). A literature survey revealed that a brief study was carried out on thermolysis of β‐sulfinyl ester to emphasize the influence of carboxylate group in the sulfenic acid formation via trapping the sulfenic acid with selected alkynes [10d–h,12] . However, to the best of our knowledge, the comprehensive study exploring the synthetic utility of various β‐sulfinyl esters with a wide range of alkynes and detailed mechanistic studies has not been realized yet.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, A. D. Dilman 58 et al (Scheme 1) reported a convenient protocol for the visible light-promoted thiol-ene click reaction. The proposed strategy has a wide substrate scope, which prescribes the use of stoichiometric ratio of thiol (1) and alkene (2) involving the lewis basic nature of the photocatalyst. The driving force for initiating the entire reaction is a protoncoupled electron transfer within the complex between the thiol and the Lewis base catalyst.…”
Section: Thiol-ene Reactionmentioning
confidence: 99%
“…1a-e Sulphur-containing organic molecules nd widespread utilization in various elds of chemistry. 2,3 With an increase in the number of approved organosulphurbased drugs, several studies have been carried out with the aim of introducing the sulphur functional unit in organic molecules. 4,5 Among organosulphur compounds, vinyl sulfones have been signicantly important due to their unique structural motif, which is valuable for designing building blocks in materials science and pharmaceutical science, as well as their intrinsic electron-withdrawing nature; moreover, they serve as functional modulators in various synthetic transformations.…”
Section: Introductionmentioning
confidence: 99%